SURVEY ALUMNI JURUSAN KESEHATAN MASYARAKAT UNSOED - Ngadiman, Ngadiman; Fitria, Agnes; Gamelia, Elviera; Ulfah, Nur (Kesmas Indonesia: Jurnal Ilmiah Kesehatan Masyarakat, 2010)
Departement of Public Health since 2001 until 2008 has graduated about 265 people. However, during this period has never been treasure study activities and stakeholder satisfaction. Treasure was necessary for study and satisfication of stakeholders in order to improve the quality the graduateds and the public trust. This study used quantitative and qualitative research approaches. Samples was taken with a total population approach with consideration to avoid at least the data collected. Treasure results indicate that the Departement of Public Health curriculum can be used in the world of work but still need to increase competence as field work alumni. The average waiting period for alumni to get a job is 7 month. Alumni earned income : <1 million per month of 27,8%, between 1-2 million per month amounting to 36,1% and >2 million per month sebesar 19,4% and are not income of 16,7%. The main competence of graduatesof the alumni needed by users is the ability to identify health problems, plan, implement and evaluate health programs ontheir respective specialization.